Widening participation in medicine? New insights from school students' aspirations. Issue 2 (9th November 2017) - Gore, Jennifer; Patfield, Sally; Holmes, Kathryn; Smith, Maxwell
Abstract : Objectives: Students from lower socio‐economic status backgrounds continue to be under‐represented in medical education. Although various initiatives have been implemented by universities to widen participation, their effectiveness and their timing remain contentious. Prior studies have primarily focused on students already on a medical pathway, with little analytical attention given to the aspirations of primary and secondary school‐aged students. The aim of this study was to identify the characteristics of students who express early interest in medicine and ascertain the degree to which diversification of the future medical student cohort is indicated. Methods: As part of a longitudinal study of educational and occupational aspirations (2012–2015), students in Years 3–12 ( n  =   6492) from government schools in New South Wales, Australia, completed an annual online survey. Their individual responses were linked with prior academic achievement and demographic data. Logistic regression models were used to examine the significance of student‐ and school‐related variables as predictors of interest in medicine. Results: Significant predictors were: being in the early years of secondary school, possessing high cultural capital, coming from a language background other than English, being female, and perceiving oneself as 'well above average' relative to peers. Socio‐economic status was a significant predictor when examined independently, but not when all variables were considered in the full regression model. Conclusions: For medical schools seeking to widen participation, this study underscores the importance of recognising the intersection of other factors with socio‐economic status and how they contribute to students' aspirational biographies. If medical schools are to select from a more diverse range of applicants, recruitment strategies must take into account the discursive positioning of the discipline. Sustained outreach into primary and secondary schools may be critical to interrupting the current social reproduction of medical schooling. Abstract : The authors investigated the characteristics of students aged 8—18 years who expressed interest in medicine and found few indications that medical education will attract a more diverse student